Analysis of the implementation of contextual teaching and learning components in Islamic education and characters textbook SMK class X - Hilwati; Zulfani Sesmiarni; Iswantir M.; Zetty Nurzuliana Rashed (Penerbit Universiti Kebangsaan Malaysia, 2023)
Islamic Education Teachers of SMKN 2 Padang Panjang use Islamic Education and Characters Textbook published by the Erlangga Publisher to convey the material to Grade Ten students. Contextual teaching and learning approaches are implemented by teachers to assist them in associating a material according to the student’s real life situation by involving seven key components namely constructivism, inquiry, questioning, learning community, modelling, reflecting and authentic assessment. This study aims to find out the implementation of contextual teaching and learning components in the Islamic Education and Characters textbook of SMK Class X published by the Erlangga Publisher. This study employs a descriptive qualitative approach by analysing the Islamic Education and Characters textbook based on the seven components of contextual teaching and learning approaches. The data of this study has been collected through the marking of the scoring sheet which is concentrated on the scoring criteria on each contextual teaching and learning component. Then, the data obtained was analysed by the percentage scores of each aspect of the seven approach components. The results show that the Islamic Education and Characters textbook of SMK Class X published by the Erlangga Publisher was compiled based on the contextual teaching and learning approach with the following percentage: 80% for constructivism; 100% for inquiries; 91.6% for questioning; 100% for the learning community; 78.3% for modelling; 100% for reflection; and 100% for authentic assessment.